2001
DOI: 10.1161/01.hyp.37.6.1458
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Na-Cl Cotransporter Reduce Blood Pressure in Humans

Abstract: Abstract-The relationship between salt homeostasis and blood pressure has remained difficult to establish from epidemiological studies of the general population. Recently, mendelian forms of hypertension have demonstrated that mutations that increase renal salt balance lead to higher blood pressure, suggesting that mutations that decrease the net salt balance might have the converse effect. Gitelman's syndrome, caused by loss of function mutations in the Na-Cl cotransporter of the distal convoluted tubule (NCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
6
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 10 publications
(16 reference statements)
6
110
6
1
Order By: Relevance
“…The frequencies of the 180K, 569V, and 849H alleles were unexpectedly high: 1.51, 0.38, and 1.27%, respectively. Blood pressure levels of heterozygous subjects with the GS mutations were not significantly different from those of wild-type subjects, which agreed with the study by Cruz et al (2). However, we could not re-examine the observation by Cruz et al that younger (<18 years) subjects heterozygous for a GS mutation had lower blood pressure levels, since our study population consisted of subjects more than 30 years old.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The frequencies of the 180K, 569V, and 849H alleles were unexpectedly high: 1.51, 0.38, and 1.27%, respectively. Blood pressure levels of heterozygous subjects with the GS mutations were not significantly different from those of wild-type subjects, which agreed with the study by Cruz et al (2). However, we could not re-examine the observation by Cruz et al that younger (<18 years) subjects heterozygous for a GS mutation had lower blood pressure levels, since our study population consisted of subjects more than 30 years old.…”
Section: Discussionsupporting
confidence: 88%
“…However, we could not re-examine the observation by Cruz et al that younger (<18 years) subjects heterozygous for a GS mutation had lower blood pressure levels, since our study population consisted of subjects more than 30 years old. Although heterozygous GS mutations do not influence blood pressure levels in Japanese, homozygous GS mutations are expected to reduce blood pressure levels, as reported by Cruz et al (2) and as suggested by our observation that a subject with possible compound heterozygous mutations (180K and 849H) had a low blood pressure level. If we accept the 8 GS mutations reported in Japanese (6-9), the combined frequency of these mutations would be (56 14 1 Values are expressed as mean (SEM).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We have shown that the carrier state for rare functional mutations in NCCT, NKCC2 and ROMK reduce blood pressure in FHS participants. Each of these genes governs renal salt handling, and homozygous loss of function mutations in them lower blood pressure by reducing salt reabsorption; heterozygous mutations in NCCT have also been shown to increase renal salt loss 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous carriers of these mutations are normotensive but do actually consume more salt, again underscoring the tight interaction of genetic and environmental factors to blood pressure regulation. While homozygous carriers of Gitelman's or Bartter's mutations suffer from severe disorders, there is speculation that heterozygotes or carriers of other mutations that cause only mild inhibition of such transporters are protected against hypertension (Cruz et al 2001). In addition to this considerable number of loss-offunction mutations in these ion transport proteins, a gain-offunction mutation in CLCNKB has been reported that causes a conservative amino acid substitution (T481S; Fig.…”
Section: Monogenic Hypotensionmentioning
confidence: 99%